Jogos teatrais para formação de educadores em museus - Amanda Ribeiro Marzano (2023)
This project seeks to analyze the following hypothesis: theatrical improvisation has the potential to contribute to the training of Museum Educators. To analyze this hypothesis, a course was created entitled “Topics in Creative Processes A - Theatrical games for art educators and mediators” within the scope of Transversal Training at UFMG. The discipline process had as a methodology to use the theatrical games developed by the author Viola Spolin and to discuss how the games help in the practice of museum educators. During the course classes, a very enriching place for the exchange of knowledge, learning and experiences was established for students and educators. The data were collected from video recordings of classes and notes in a fieldwork notebook. Based on the analysis of the students' experience and speeches in this course, we wrote a booklet aimed at educational professionals in museums.